Marketing plan for neo-ethnic textile - Cometa, Romeo M. Jr (University of the Philippines Diliman, 2014)
This paper attempts to devise a marketing plan and the technology for neo-ethnic textile launched by the Philippine Textile Research Institute (PTRI) to possible adaptor who is willing to commercialize the product. The local and international markets were analyzed. The strategies being used, were crafted vis-a-vis the strategic objective of the marketing plan. Customade Craft Center (CMCC) being the possible adaptor caters globally competitive and innovative textiles to the Philippine market, especially as export market. It aims to be the first in the market to introduce natural-based, handcrafted fabric with the intervention of science and technology (S&T) to produce a neo-ethnic fabric. Ethnic textile is traditionally worn by all, across generation of tribes, gender, income, occupation and education of all member of tribes located in Southern part of the Philippines. The concept of "Neo-Ethnic" is not necessarily a product but the story behind the way it is crafted and made. Neo-ethnic is the combination of the traditional ethnic textile plus the science and technology intervention of PTRI will come out into a brand name of "Neo-ethnic" product which is new from the old traditional ethnic textile that are more fashionable, elegance and functionality. These are the market needs that are being addressed by the neo-ethnic fabric offering. Since, it is the first of its kind, there is no market data available, but the market growth of similar product like "Batik" was looked into and discussed in the review of related studies and report. After analyzing the market, the capabilities, areas of advantage, as well strength, weaknesses of the agency were tackled. External opportunities and threats were likewise discussed. PTRI is an agency of the Department of Science and Technology with a sizeable amount of tangible assets and the area of competitive advantage in the processing of textile and technology services. The mechanical and chemical processing section provides technical services such as spinning, handloom weaving, development of weave designs, fabrication of handloom/ancillary equipment and loom accessories. PTRI also provides technology transfer services by way of technical trainings to the micro, small and medium enterprises (MSMEs) and to Institute's other clients like government instrumentalities, the academe and other private enterprises. PTRI continues research and development program does not end with green textile. It continually strives to expand its R&D and introduce new offering to the adaptor such as smart textile and intelligent textile. Both of the two (2) basic promotion strategies of "push" and "pull" approaches shall be implemented. The distribution channels will be tapped to promote or push the product. A limited number of neo-ethnic fabric will be directly display to high-end malls, hotels and resorts shops. It is a way of creating awareness on the availability of the product and later creating the demand. In the second approach, the firm will undertake promotional activities to entice more customers. Promotional activities include participation in trade fair, fashion shows, advertising via Information Communication Technology (ICT)-based marketing platform, establishment of digital marketing strategy and collaboration with partners and supporters.